Role of CORO1A in Regulating Immune Homeostasis of Mammary Glands and Its Contribution to Clinical Mastitis Development in Dairy Cows - Bohao Zhang; Na Chen; Xing Yu; Jianfu Li; Weitao Dong; Yong Zhang; Xingxu Zhao; Quanwei Zhang (Biomolecules)
Immune homeostasis refers to the immune system’s ability to maintain a dynamic balance, defend against infections while preventing excessive inflammation, and preserve normal physiological activity. However, its regulatory role in the mammary glands (MGs) of cows with clinical mastitis (CM) remains unclear. This study examined MG tissue samples collected from healthy Holstein cows and those with CM caused by Staphylococcus aureus (n = three per group) to identify candidate biomolecular targets involved in immune homeostasis in dairy cows affected by mastitis through a proteomics-based bioinformatic analysis and analyze their expression and localization in MG tissues. A pathological examination revealed that the MG tissues of the CM group exhibited significant alveoli collapse and inflammatory cell infiltration. The presence of activated phagolysosomes and lysosomes indicated active immune and phagocytic responses. Bioinformatics highlighted coronin1A (CORO1A) as a potential modulator of immune responses through phagosome formation. Dysregulation could impair immune homeostasis, thereby exacerbating mastitis. Immunofluorescence and immunohistochemistry staining showed that CORO1A was localized in monocytes, macrophages, and neutrophils. Molecular mechanism analysis revealed that Toll-like receptor 2 (TLR2) recognizes pathogens and recruits CORO1A to the phagosome formation site, thereby enhancing the phagocytic activity of immune cells. The expression levels of CORO1A and TLR2 mRNA and proteins were positively correlated with the incidence of mastitis. In conclusion, CORO1A upregulation may activate immune and phagocytic responses, disrupting MGs’ immune homeostasis during Staphylococcus aureus-induced mastitis. These findings provide novel insights into mastitis pathogenesis and potential therapeutic targets.